Two New Species of the Mite Genus Stereotydeus Berlese, 1901 (Prostigmata: Penthalodidae) from Victoria Land, and a Key for Identification of Antarctic and Sub-Antarctic Species - Claudia Brunetti; Henk Siepel; Pietro Paolo Fanciulli; Francesco Nardi; Peter Convey; Antonio Carapelli (Taxonomy, 2021)
Two new mite species belonging to the genus Stereotydeus Berlese, 1901 were discovered from locations along the coast of Victoria Land, continental Antarctica. Previous records of this genus in the area under study only reported the presence of S. belli and S. mollis. Although those studies included no morphological analyses, it has since been assumed that only these species were present within the area. Specimens of S. ineffabilis sp. nov. and S. nunatakis sp. nov. were obtained, sometimes in sympatry, from four different localities in Central and South Victoria Land and are here described and illustrated using optical and scanning electron microscopy (SEM) techniques. Features useful for identification of the two new Stereotydeus species include the size of the specimens, the length of the apical segment of pedipalps, the presence/absence of division of the femora, the position of solenidia, the shape and disposition of the rhagidiform organs on the tarsi, the shape of the apical setae of the tarsi, the numbers of aggenital setae and the position of the anal opening. A key to 14 of the 15 currently described Antarctic and sub-Antarctic Stereotydeus species is provided.